Hypercoagulable State Induced in Humans by the Intravenous Administration of Purified Ellagic Acid - Girolami, A; Cliffton, E. E (Thrombosis and Haemostasis, 1967)
The intravenous administration of ellagic acid induces a hypercoagulable state in humans. This is characterized by a striking shortening of the silicone clotting time and moderate shortening of the glass clotting time. No change in other coagulation parameter was noted. However, in one patient with a prolonged thromboplastin generation test, a correction of same was observed. The effect of ellagic acid is more prolonged in humans than in animals. There was no obvious toxic reaction to the administration of the drug.